CAR T-cell-associated neurotoxicity in central nervous system hematologic disease: Is it still a concern? - Velasco, Roser; Mussetti, Alberto; Villagrán-García, Macarena; Sureda, Anna (Frontiers in Neurology, 2023)
Chimeric antigen receptor (CAR) T-cell systemic immunotherapy has revolutionized how clinicians treat several refractory and relapsed hematologic malignancies. Due to its peculiar mechanism of action, CAR T-cell-based therapy has enlarged the spectrum of neurological toxicities. CAR T-cell-associated neurotoxicity—initially defined as CAR T-cell-related encephalopathy syndrome (CRES) and currently coined within the acronym ICANS (immune effector cell-associated neurotoxicity syndrome)—is perhaps the most concerning toxicity of CAR T-cell therapy. Importantly, hematologic malignancies (especially lymphoid malignancies) may originate in or spread to the central nervous system (CNS) in the form of parenchymal and/or meningeal disease. Due to the emergence of deadly and neurological adverse events, such as fatal brain edema in some patients included in early CAR T-cell trials, safety concerns for those with CNS primary or secondary infiltration arose and contributed to the routine exclusion of individuals with pre-existing or active CNS involvement from pivotal trials. However, based primarily on the lack of evidence, it remains unknown whether CNS involvement increases the risk and/or severity of CAR T-cell-related neurotoxicity. Given the limited treatment options available for patients once they relapse with CNS involvement, it is of high interest to explore the role of novel clinical strategies including CAR T cells to treat leukemias/lymphomas and myeloma with CNS involvement. The purpose of this review was to summarize currently available neurological safety data of CAR T-cell-based immunotherapy from the clinical trials and real-world experiences in adult patients with CNS disease due to lymphoma, leukemia, or myeloma. Increasing evidence supports that CNS involvement in hematologic disease should no longer be considered per se as an absolute contraindication to CAR T-cell-based therapy. While the incidence may be high, severity does not appear to be impacted significantly by pre-existing CNS status. Close monitoring by trained neurologists is recommended.